2017
DOI: 10.1007/s11224-017-0939-6
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Si–H ⋯ B charge-inverted hydrogen bonds in 1-silacyclopent-2-enes and 1-silacyclohex-2-enes

Abstract: It is shown that the H· · · B contacts in 1-silacyclohex-2-enes are clearly stabilizing and strong, whereas those in 1-silacyclopent-2-enes are much weaker. This result is supported by analysis of QTAIM-based parameters and appropriate structural changes taking place upon the open form → closed form transformation and is in full agreement with previous NMR spectroscopic data [Wrackmeyer et al. (2006) Appl Organometal Chem 20:99-105]. Also, the influence of electronic and steric effects originating from the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 61 publications
(99 reference statements)
2
25
0
Order By: Relevance
“…Importantly, this also shows that hydride‐triel bond may have significant role in molecular binding and in determining molecular structure. For example, most recently we have shown that the SiH⋯B contacts in some 1‐silacyclohex‐2‐enes are clearly stabilizing and strong with interaction energies of the order of 4–5 kcal/mol—the result in a full agreement with earlier studies by Wrackmeyer et al based on NMR spectroscopic data. Moreover, these energies can even be enhanced to 13–14 kcal/mol if 9‐borabicyclo[3.3.1]nonane group is substituted by the BH 2 one (see Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, this also shows that hydride‐triel bond may have significant role in molecular binding and in determining molecular structure. For example, most recently we have shown that the SiH⋯B contacts in some 1‐silacyclohex‐2‐enes are clearly stabilizing and strong with interaction energies of the order of 4–5 kcal/mol—the result in a full agreement with earlier studies by Wrackmeyer et al based on NMR spectroscopic data. Moreover, these energies can even be enhanced to 13–14 kcal/mol if 9‐borabicyclo[3.3.1]nonane group is substituted by the BH 2 one (see Fig.…”
Section: Resultssupporting
confidence: 91%
“…As a consequence, the main purpose of this article is to see how the strength of the H⋯Y hydride‐triel bond in systems investigated here can be influenced by substituents attached to X and Y, that is R X and R Y , respectively. Moreover, this is also to show that hydride‐triel bonds can be strong enough to considerably determine structure and properties of molecular systems …”
Section: Introductionmentioning
confidence: 95%
“…Unfortunately, they formed a new product with the triel donor molecule. It was also demonstrated that a weakly polarized Si–H bond can bind with a strong hydrogen‐bond donor in solution . Therefore, the Si–H bond in SiHMe 3 is introduced to the triel donor atom in ZX 3 (Z = B and Al; X = H and Me).…”
Section: Resultsmentioning
confidence: 99%
“…Triel bonding exhibits some surprising cooperativity with other types of interactions including hydrogen, halogen, pnicogen and tetrel bonds since the binding distance in the strong triel bond undergoes a prominent contraction. Numerous studies have demonstrated that the intramolecular Si–H···B bridge can maintain the conformation of compounds simultaneously containing silicon and boron atoms …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation